Characteristic Body Mass Index and Nutrition Knowledge of Snack Food School-Age Children Among Elementary School Students at SD Ciawi Jatinangor - Fifi Veronica; Resti Gradia; Wulan Mayasari; Nandina Oktavia (Fakultas Kedokteran Universitas Sriwijaya, 2020)
AbstractIntroduction. Lack of nutrient in school age children in several times had implication in abnormal increasing body weight and height related with their growth. Snack food school –age children had contribute 15-20% from total daily nutrien consumption. Aim of this study is to describe characteristic body mass index and nutrition knowledge about healty snack food school age. Method.Collecting primary data with cross sectional descriptive study comes from questionnaire, measurement of body weight and height.Number of total sampling 33 participants from grade 5 elementary school Ciawi Jatinangor. The questionnaire were asked about characteristics participants, nutritional knowledge and their reasoning and preference for variety of snack food school-age children. It also include question about their self efficacy about their knowledge. Results The result shows most of participants, male and female in underweight status. The mostly reasoning choice snacking school variety cause of their tastefull, cheaper and umami. Number they pocket money not correlated with their skill to choices variety of school snacking. Conclusion. The present study revealed that, 36% and 39% of boys and girls respectively were having underweight BMI with lack of healthy characteristical knowledge of snack food school aged. Participants tends to show good self efficacy about their snacking food. Changing student food behavior and their efficacy will require cooperation supports between school staff, parents and food vendors at schoolKeywords : Body Mass Index, Nutrition knowledge, Snack food School-Age Children AbstrakKurangnya zat gizi pada anak usia sekolah dalam waktu yang lama dapat berimplikasi pada terganggunya penambahan berat badan dan tinggi badan seorang anak yang sedang bertumbuh. Salah satu pemenuhan zat gizi harian yang penting adalah lewat kontribusi zat gizi Pangan Jajanan Anak Sekolah(PJAS) antara 15-20%.Penelitian ini bertujuan untuk mengetahui gambaran karakteristik status gizi (body mass index) dan tingkat pengetahuan PJAS pada anak sekolah dasar di Jatinangor.. Penelitian ini merupakan penelitian potong lintang deskriptif dengan menggunakan data primer melalui kuesioner dan pengukuran berat badan dan tinggi badan.Jumlah total sampling yang diambil sekitar 33 orang siswa kelas 4 SD Ciawi Jatinangor. Hasil penelitian menunjukkan sebagian besar siswa berada pada status gizi kurang (underweight) baik pada laki-laki maupun perempuan. Alasan terbesar para siswa memilih jenis makanan PJAS adalah karena rasanya enak dan harganya murah. Besaran uang saku yang mereka bawa setiap harinya tidak berkorelasi dengan ketrampilan mereka dalam menentukan jenis PJAS. Perlu kerjasama yang baik antara pihak sekolah, orangtua murid dan pedagang makanan di ingkungan sekolah untuk membentuk prilaku jajan yang baik dan self efficacy yang baik pada siswa.Kata kunci :Body Mass Index, karakteristik pengetahuan jajanan , pangan jajanan anak sekolah